Parametric Meta-Technology Frameworks to Study Technical Efficiency and Macro-Economic Effects in the European Banking System - Bilel Jarraya (Contemporary Economics)
Bank efficiency scores usually serve as a tool for comparing institutions with each other while allowing us to quantify sub-optimal decision-making unit choices. In the case of inter-country comparisons, such differences can also arise because of macro-economic heterogeneity between countries. Previous studies estimated a common technology limit for a sample of banking institutions in different countries. The contribution of our paper is that we employ a parametric approach to specify meta-frontiers and to study the effect of macro-economic heterogeneity on banking technology development. First, we use a parametric directional distance function to specify the appropriate technology frontier for each nation and the meta-technology frontier that includes all country-specific frontiers. Then, we define the directional technology gap ratio referring to the inefficiency scores evaluated from meta-technology and country-specific technology frontiers. The estimated parameters are more significant in our model than in the general model, also called the common frontier model. Comparing the results of our model to those of common frontiers, we find a substantial variation not only in inefficiency scores but also in countries’ rankings. While resorting to a pooled linear regression model, we demonstrate that the assessed technology gap ratio exhibits a significant association with inflation rates and per capita GDP. This result proves the influence of macro-economic heterogeneity on banks’ efficiency and technological development.